Repulsions instruct synaptic partner matching in an olfactory circuit - Zhuoran Li; Cheng Lyu; Chuanyun Xu; Ying Hu; David J. Luginbuhl; Asaf B. Caspi-Lebovic; Jessica M. Priest; Engin Özkan; Liqun Luo (Nature, 2026)
Abstract Neurons exhibit extraordinary precision in selecting synaptic partners. Although cell-surface proteins (CSPs) that mediate attractive interactions between developing axons and dendrites have been shown to instruct synaptic partner matching 1,2 , the degree to which repulsive interactions have a role is less clear. Here, using a genetic screen guided by single-cell transcriptomes 3,4 , we identified three CSP pairs, Toll2–Ptp10D, Fili–Kek1 and Hbs/Sns–Kirre, that mediate repulsive interactions between non-partner olfactory receptor neuron (ORN) axons and projection neuron (PN) dendrites in the developing Drosophila olfactory circuit. Each CSP pair exhibits inverse expression patterns in the select ORN–PN partners. Loss of each CSP in ORNs led to similar synaptic partner matching deficits as the loss of its partner CSP in PNs, and mistargeting phenotypes caused by overexpressing one CSP could be suppressed by loss of its partner CSP. All CSP pairs are also differentially expressed in other brain regions. Together, our data reveal that multiple repulsive CSP pairs work together to ensure precise synaptic partner matching during development by preventing neurons from forming connections with non-cognate partners.